2022
DOI: 10.1002/wnan.1836
|View full text |Cite
|
Sign up to set email alerts
|

Engineering gold nanoparticles for molecular diagnostics and biosensing

Abstract: Advances in nanotechnology and medical science have spurred the development of engineered nanomaterials and nanoparticles with particular focus on their applications in biomedicine. In particular, gold nanoparticles (AuNPs) have been the focus of great interest, due to their exquisite intrinsic properties, such as ease of synthesis and surface functionalization, tunable size and shape, lack of acute toxicity and favorable optical, electronic, and physicochemical features, which possess great value for applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 217 publications
0
15
0
Order By: Relevance
“…First, the concept and function of biosensors are described, followed by the special physical, chemical, and optical properties of nanomaterials and their advantages in biosensing. Besides, this paper focuses on applying common nanomaterials in biosensors, mainly including Au NPs, 25,26 CNTs, [27][28][29] QDs, 30,31 graphene, 32 and magnetic nanobeads. 33 We also emphasize the role played by nanotechnology in the design of various biosensors (electrochemical 34,35 and optical biosensors 36,37 ) and provide some typical cases to summarize the advantages and detection principles of incorporating nanomaterials in sensors, which are applied to enhance the sensitivity and improve the stability of sensors, to reduce background noise and to scale down the detection time.…”
Section: Introductionmentioning
confidence: 99%
“…First, the concept and function of biosensors are described, followed by the special physical, chemical, and optical properties of nanomaterials and their advantages in biosensing. Besides, this paper focuses on applying common nanomaterials in biosensors, mainly including Au NPs, 25,26 CNTs, [27][28][29] QDs, 30,31 graphene, 32 and magnetic nanobeads. 33 We also emphasize the role played by nanotechnology in the design of various biosensors (electrochemical 34,35 and optical biosensors 36,37 ) and provide some typical cases to summarize the advantages and detection principles of incorporating nanomaterials in sensors, which are applied to enhance the sensitivity and improve the stability of sensors, to reduce background noise and to scale down the detection time.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, research on nano-bio interaction has been significantly increasing. It is essential to comprehend how nanoparticles (NPs) interact with the biomimetic systems and how stable they are in order to advance a number of biomedical applications. Because of their small size, simplicity of surface ligand functionalization, low toxicity, and high volume to mass ratio, Au NPs have been widely used in optics, biosensing, and medical science, particularly drug delivery, genetics, and other applications such as colorimetric biosensors, , the photothermal effect, fluorescence quenching, and catalysis. , However, there are ongoing debates about how well Au NPs work in biological systems as well as about how they affect the environment and human health. It has been previously reported that due to the enormous prevalence of diverse proteins in the biological system, “protein corona” is formed, which is most popular and has been extensively researched. When NPs are exposed to biological fluid in the body, several proteins instantly form protein corona on the surface of the NPs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7,8 ] As such, AuNPs have the potential for extensive medical applications in diagnosis and treatment. In pre‐clinical settings, the use of AuNPs includes point‐of‐care diagnostics [ 9,10 ] (lateral flow assays such as pregnancy tests and rapid COVID‐19 tests), in vivo imaging [ 11,12 ] (photoacoustic and computerised tomography), and therapeutics [ 13–15 ] (photothermal therapy, radiotherapy, catalytic therapy, and drug delivery). Although AuNPs treatment designs and applications are rapidly developing with some having reached clinical trials, [ 16–18 ] none has yet been approved for clinical use primarily because it is hard to predict the changes that nanoparticles undergo and how they behave in complex biological systems.…”
Section: Introductionmentioning
confidence: 99%